A clinical report of solitary gingival overgrowth in a young female patient - Hemalatha Ramakrishnan; Anisa Noorullah; Leelarani Venugopal (Wolters Kluwer Medknow Publications, 2019)
Pyogenic granuloma is a type of inflammatory hyperplasia. The term "inflammatory hyperplasia" is used to describe nodular growths of oral mucosa that histologically contain inflamed fibrous and granulation tissues. It is nonneoplastic. It is predominant in second decade of life in young adult females. Oral pyogenic granuloma is the most common gingival tumor with a striking predilection to gingiva. About one-third of the lesions occur following trauma. Poor oral hygiene may be a precipitating factor as 75% of all cases show calculus or foreign material in gingival sulcus. Lesions are more common in maxillary than mandibular gingiva; lesions are more common on the facial aspect of gingiva than gingival aspect. Clinically, pyogenic granuloma is a smooth, lobulated, exophytic lesion seen as small, red, and erythematous papules on a pedunculated or sessile base that is usually hemorrhagic. Clinical development of the lesion is slow, asymptomatic, and painless but may also grow rapidly; surface is characteristically ulcerated and friable, covered by yellow, fibrinous membrane with its color ranging from pink to red to purple depending on the age of the lesion. Pyogenic granuloma develops in about 5% of pregnancy, called as "pregnancy tumor'' or "granuloma gravidarum." Hormonal imbalance in pregnancy exaggerates the body's response to bacterial irritation. Sometimes, pregnancy gingivitis may show a tendency for localized hyperplasia, which is called "pregnancy granuloma." Generally, it appears in about second-to-third month of pregnancy. Although pyogenic granuloma is a nonneoplastic growth in the oral cavity, proper diagnosis, prevention, management, and treatment of the lesion is very important. Excisional surgery is the treatment of choice whereas cryosurgery, excision by Nd:YAG laser, and sclerotherapy are alternative therapies. Though pyogenic granuloma in pregnancy is because of the effect of sex hormonal imbalances, taking careful oral hygiene measures is important to avoid recurrence of the lesion. This article is a case report of a 22-year-old female patient with pyogenic granuloma in the buccal aspect of maxillary gingiva managed by surgical excision.